Idiopathic Pericarditis and Pericardial Effusion in Children: Contemporary Epidemiology and Management - Shakti, Divya (J Am Heart Assoc, 2014)
BACKGROUND: Multicenter studies on idiopathic or viral pericarditis and pericardial effusion (PPE) have not been reported in children. Colchicine use for PPE in adults is supported. We explored epidemiology and management for inpatient hospitalizations for PPE in US children and risk factors for readmission. METHODS AND RESULTS: We analyzed patients in the Pediatric Health Information System database for (1) a code for PPE; (2) absence of codes for underlying systemic disease (eg, neoplastic, cardiac, rheumatologic, renal); (3) age ≥30 days and <21 years; and (4) discharge between January 1, 2007, and December 31, 2012, from 38 hospitals contributing complete data for each year of the study period. Among 11 364 hospitalizations with PPE codes during the study period, 543 (4.8%) met entry criteria for idiopathic or viral PPE. Significantly more boys were noted, especially among adolescents. No temporal trends were noted. Median age was 14.5 years (interquartile range 7.3 to 16.6 years); 78 patients (14.4%) underwent pericardiocentesis, 13 (2.4%) underwent pericardiotomy, and 11 (2.0%) underwent pericardiectomy; 157 (28.9%) had an intensive care unit stay, including 2.0% with tamponade. Median hospitalization was 3 days (interquartile range 2 to 4 days). Medications used at initial admission were nonsteroidal anti‐inflammatory drugs (71.3%), corticosteroids (22.7%), aspirin (7.0%), and colchicine (3.9%). Readmissions within 1 year of initial admission occurred in 46 of 447 patients (10.3%), mostly in the first 3 months. No independent predictors of readmission were noted, but our statistical power was limited. Practice variation was noted in medical management and pericardiocentesis. CONCLUSIONS: Our report provides the first large multicenter description of idiopathic or viral PPE in children. Idiopathic or viral PPE is most common in male adolescents and is treated infrequently with colchicine.